THE URGENCY OF APPLYING JOURNALISTIC ETHICS IN ONLINE ISLAMIC MEDIA REPORTING ACTIVITIES: A CONCEPTUAL STUDY - Fitri - Fitri; Adeni - Adeni (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2020)
This article aims to study the urgency of applying journalistic ethics in online Islamic media activities. The study focuses on analyzing the seven standards of Islamic Media Literacy from Indonesian Ministry of Religion, namely (1) principles of online news production, (2) news distribution ethics, (3) accuracy and anti hoax, (4) the spirit of amar ma'ruf nahyi munkar, (5) principle of wisdom in da'wah, (6) principles in digital interaction, and 7) principle of press freedom. By using the qualitative method of library research, we argue that these seven principles could be said as journalistic ethics that must be applied in Islamic media reporting activities. These values are extremely important for Islamic media activities because the credibility of journalists and media institutions is related to public assessment which is quite determining the continuity of media life. The news in online Islamic media has different characteristics from other media. Online Islamic media cannot avoid how a text or symbol is presented in the category of fundamentalism-radicalism or moderate Islamic ideology. Problems arise when the radical Islamic ideology is more dominant than moderate Islamic ideology so that it is not uncommon for the Islamic media to get caught up in provocative actions which in some limits create disharmony for people's lives. If that is the case, the application of peaceful journalistic values becomes important to display Islamic da'wah of rahmatan li alamin.